Ecological Value Of Soil Organic Matter (SOM) at Tropical Evergreen Aglaia-Streblus Forest of Meru Betiri National Park, East Java, Indonesia - Sulistiyowati, Hari; Winarso, Sugeng; Macandog, Damasa; Sotto, Rachel; Baguinon, Nestor; Buot Jr, Inocencio (JOURNAL OF TROPICAL SOILS, 2016)
As part of carbon pools, forest soil stores soil organic matter (SOM) that contains many elements including organic C, N, P, and K. These elements contribute nutrients for biogeochemical cycles within the ecosystem. This study was done to determine the ecological value of forest soil organic matter at tropical evergreen Aglaia-Streblus forest of Meru Betiri National Park (MBNP), East Java, Indonesia. The data were sampled along gradient topography in Pringtali tropical forest of TMBNP. Direct measurements of soil moisture, temperature, and pH were taken in the field. The soil samples were extracted from 6 points of soil solum using soil auger, and then oven-dried to get value of dry-weight. The elements content of organic C, N, P, and K were analyzed and estimated at the laboratory. The ecoval of SOM was appraised using developed ecological valuation tool. The result showed that SOM contributed higher ecoval of organic C (66.03 Mg ha-1) than other elements. Compared to P and K elements, N had the highest stock of element content. However, comparing to other two tropical forest ecosystems of Asia the ecoval of SOM elements in TMBNP was relatively low because of its natural geomorphological features.The ecoval of SOM elements in TMBNP was relatively low because of its natural geomorphological features. The ecovals contributed about 2.440,64 - 6.955,50 USD or 31.271.923,73 - 89.120.837,23 IDR per hectare of ecological value (d) to the ecosystem. This value was mainly contributed by organic C stock in the TMBNP forest SOM. It means the forest SOM had higher element content of organic C than N, P, and K elements. This d value is an indicator for TMBNP to protect the SOM elements meaning protecting their resources to sustain the biogeochemical cycles in the forest ecosystem. All the management and policy correlated to this protected area should consider this valuable information for their plan and actions.